Association between retinal thickness measured by spectral-domain optical coherence tomography (OCT) and rod-mediated dark adaptation in non-exudative age-related maculopathy. Issue 10 (2nd February 2011) - Clark, Mark E; McGwin, Gerald; Neely, David; Feist, Richard; Mason, John O; Thomley, Martin; White, Milton F; Ozaydin, Bunyamin; Girkin, Christopher A; Owsley, Cynthia
Abstract : Aim: To examine associations between retinal thickness and rod-mediated dark adaptation in older adults with non-exudative age-related maculopathy (ARM) or normal macular health. Methods: A cross-sectional study was conducted with 74 adults ≥50 years old from the comprehensive ophthalmology and retina services of an academic eye centre. ARM presence and disease severity in the enrolment eye was defined by the masked grading of stereofundus photos using the Clinical Age-Related Maculopathy grading system. High-definition, spectral-domain optical coherence tomography was used to estimate retinal thickness in a grid of regions in the macula. Rod-mediated dark adaptation, recovery of light sensitivity after a photo-bleach, was measured over a 20-min period for a 500 nm target presented at 5° on the inferior vertical meridian. Main outcomes of interest were retinal thickness in the macula (μm) and parameters of rod-mediated dark adaptation (second slope, third slope, average sensitivity, final sensitivity). Results: In non-exudative disease retinal thickness was decreased in greater disease severity; thinner retina was associated with reductions in average and final rod-mediated sensitivity even after adjustment for age and visual acuity. Conclusions: Impairment in rod-mediated dark adaptation in non-exudative ARM is associated with macular thinning.